2011
DOI: 10.1093/europace/eur038
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation of atrial fibrillation in patients with therapeutic oral anticoagulation treatment

Abstract: Transseptal puncture and AF ablation can be performed safely in patients with ongoing OAT without intracardiac echocardiographic guidance and ACT monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…In the patients treated with non-vitamin K antagonist oral anticoagulants, the last dose was administered 24 h before the procedure, and the therapy was reintroduced up to 6 h after the procedure. Antithrombotic treatment with heparin was conducted in accordance with the typical scheme, with the monitoring of activated clotting tine, without reversing the effect of heparin at the end of the procedure [4,5]. …”
Section: Methodsmentioning
confidence: 99%
“…In the patients treated with non-vitamin K antagonist oral anticoagulants, the last dose was administered 24 h before the procedure, and the therapy was reintroduced up to 6 h after the procedure. Antithrombotic treatment with heparin was conducted in accordance with the typical scheme, with the monitoring of activated clotting tine, without reversing the effect of heparin at the end of the procedure [4,5]. …”
Section: Methodsmentioning
confidence: 99%
“…Subsequent data emerged that showed that bleeding complications were actually lower with uninterrupted warfarin compared with a bridging strategy. [37][38][39][40] In addition, uninterrupted strategies reduce both clinical and silent thromboembolic events. 41 This pattern of withholding anticoagulation around the time of the ablation also applied to the direct anticoagulants, with some studies advocating bridging and others not.…”
Section: Anticoagulationmentioning
confidence: 99%
“…Evidence that intraprocedural intracardiac echocardiography (ICE) reduces major bleeding complications when ablation is performed on therapeutic warfarin. 33,[37][38][39][40][41][42][43][44] Adapted from Santangeli et al 32 with permission of the publisher. Copyright © 2012, American Heart Association.…”
Section: Cost-effectiveness Of Ca As a First-line Therapy For Afmentioning
confidence: 99%